1982
DOI: 10.1254/jjp.32.679
|View full text |Cite
|
Sign up to set email alerts
|

A new device for the determination of microsomal cytochrome P-450 in renal tissue preparations from various species contaminated with mitochondria and hemoglobin.

Abstract: Using a spectrophotometer connected to a microcomputer, the carbon monoxide difference spectrum of renal microsomal dithionite reduced cytochrome P-450 was measured avoiding the effects of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Preliminary experiments showed minor spectral interference in the dithionite difference spectra, and therefore bias in the CYP content measurements and subsequent MPPGK estimates was unlikely when considered alongside the inter-assay variability (Matsubara et al, 1976). Furthermore, the dog kidney cortex microsomal CYP content measured in the current study using the dithionite difference method (Table 3) were comparable with a value reported using a customised spectral method (0.223 nmol/mg protein; (Ohno et al, 1982)). CYP content measured in dog liver were also in good agreement with previously published values (Smith et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Preliminary experiments showed minor spectral interference in the dithionite difference spectra, and therefore bias in the CYP content measurements and subsequent MPPGK estimates was unlikely when considered alongside the inter-assay variability (Matsubara et al, 1976). Furthermore, the dog kidney cortex microsomal CYP content measured in the current study using the dithionite difference method (Table 3) were comparable with a value reported using a customised spectral method (0.223 nmol/mg protein; (Ohno et al, 1982)). CYP content measured in dog liver were also in good agreement with previously published values (Smith et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Ensuring complete homogenization of kidney tissue, while also limiting contamination of microsomes with other sources of haemoproteins such as mitochondria, can be challenging. When measuring CYP content in kidney cortex, the low CYP levels, and potential for spectral interference from contaminating haemoproteins, makes accurate quantification challenging (Jakobsson and Cinti, 1973; Ohno et al, 1982). Preliminary experiments showed minor spectral interference in the dithionite difference spectra, and therefore bias in the CYP content measurements and subsequent MPPGK estimates was unlikely when considered alongside the inter-assay variability (Matsubara et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme Activity Assays, GSH and Total Glutathione Determinations Kidney cytochrome P-450 was measured as described by Omura and Sato [16] as modified by Ohno et al [17] who corrected for hemoglobin and mitochondria contaminations. p-Nitrophenol glucuronyl transferase was estimated in the microsomal suspension by the method of Burchell and Weatherill [18].…”
Section: Animal Treatment and Microsome Preparationmentioning
confidence: 99%